Pectic polysaccharide from corn (Zea mays L.) effectively inhibited multi-step mediated cancer cell growth and metastasis. (25th June 2015) - Jayaram, Smitha; Kapoor, Sabeeta; Dharmesh, Shylaja M.
Highlights: Corn pectin–COPP possessed potent galectin-3 inhibitory property. Galectin-3 being a key triggering molecule for initiation and establishment of metastasis. Metastasis has been known to be blocked effectively by COPP. COPP effectively also inhibited secondary metastasis of the liver. Abstract: Corn pectic polysaccharide (COPP) inhibited galectin-3 mediated hemagglutination at Minimum Inhibitory Concentration (MIC) of 4.08 μg/mL as opposed to citrus pectin (25 μg/mL), a well known galectin-3 inhibitor and lactose (4.16 μg/mL) – sugar specific to galectin-3. COPP effectively (72%) inhibited invasion and metastasis in experimental animals. In vivo results were substantiated by modulation of cancer specific markers such as galectin-3, which is a key molecule for initiation of metastatic cascade, vascular endothelial growth factor (VEGF) that enhances angiogenesis, matrix metalloproteinases 2 and 9 that are required for invasion, NF-κB, a transcription factor for proliferative potency of tumor cells and a phosphoglucoisomerase (PGI), the activity of which favors cancer cell growth. Structural characterization studies indicate the active component (relatively less acidic, 0.05 M ammonium carbonate, 160 kDa fraction) which showed antimetastatic potency in vitro with MIC of 0.09 μg/mL, and ∼45 fold increase in the activity when compared to that of COPP. Gas liquid chromatographic analysis indicated the presence of rhamnose (1%), arabinose (20%), xylose (3%), mannose (4%), galactose (54%) and uronic acid (10%) in different proportions. However, correlative data attributed galectin-3 inhibitory activity to enhanced levels of arabinose and galactose. FTIR, HPLC and NMR spectroscopic analysis further highlights that COPP is an arabinogalactan with methyl/ethyl esters. It is therefore suggested that the blockade of galectin-3 mediated lung metastasis appears to be a result of an inhibition of mixed functions induced during metastasis. The data signifies the importance of dietary carbohydrate as cancer-preventive agent. Although pectin digestibility and absorption are issues of concern, promising in vivo data provides evidence for the cancer preventive property of corn. The present study reveals for the first time a new component of corn, i.e., – corn pectin with cancer preventive activity apart from corn starch that has been in wide use for multipurpose health benefits.